HUBUNGAN ANTARA MOTIVASI BELAJAR DAN KESIAPAN BELAJAR DENGAN PRESTASI BELAJAR - Wenda Norita; Sumadi Sumadi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
Learning motivation and learning readiness in the process of learning geography are components which can not be separated each other. The process of learning should be motivated by the willingness of students to learn for changing to be better. But the fact that many students have low achievement in learning. To improve the students’ learning achievement is difficult because it related to internal factor and external factor which affected the process of learning. High students’ motivation and good readiness of learning is one of a way which is used to improve the students’ learning achievement.  The aim of this research was find out the correlation between students’ learning motivation and learning readiness with students’ geography learning achievement at the first grade of SMA Negeri 1 Kotabumi of North Lampung in the year of 2011-2012. The research method which is used in this research is co-relational method with the population were 266 students and the students who are taken as the sample are 84 students. In collecting the data used test, questionnaire, and documentation. In analyzing the data the researcher used Spearman Rank Correlation.  Based on the data analysis which done by the researcher, the result of this research shows that: 1) there is significant positif correlation between learning motivation and students’ learning achievement and the coefficient correlation (rs) is 0.626. 2) There is significant positif correlation between learning readiness and students’ learning geography achievement, meanwhile the coefficient correlation (rs) is 0.749. 3) It means that the higher of students’ learning motivation so it will make good learning readiness and there is significant positif correlation between the students’ geography learning achievement  at the first grade of SMA Negeri 1 Kotabumi of North Lampung in the year of 2011- 2012.  Meanwhile the coefficient correlation (rs) is 0.697. Key word: learning motivation, learning readiness and learning achievement